Penetrating Cardiac Injuries: Role of Emergency Thoracotomy - Ali Hais Elamery, Ihssan; Edan Kadim, Maysa (Diyala Journal of Medicine, 2019)
Background: Due to the increase in violence in recent years due to the wars and the increasing use of weapons and sharp machines such as knives and others, the number of victims of cardiac injuries, especially gunshot wounds, stabbing injuries and other acute machines has increased due to the seriousness of these injuries and complications resulting therefrom. Objective: To show the importance of urgent diagnosis and surgical approach of cardiac traumatic patients. Patients and Methods: Between January 2016 and January 2017, 5 penetrating cardiac traumatic patients were admitted to the emergency unit in Immam Hussein medical city in Karbala, 3 of them were stab wounds and 2 cases were shell injuries. All of them males in age range from 14-44 years old ,the 5 patients were operated without using cardiopulmonary bypass machine and all of them passed without any complications except one patient who complain from some neurological deficits postoperatively. Results: In this study we have 5 patients with penetrating cardiac injuries, 2 have gunshot (40%) and 3 have stab injuries (60%). Emergency thoracotomies were done in all patients and the wounded were sutured with 4/0 proline after good resuscitation in ER. Conclusion: Traumatic injuries of the heart are one of the major cause of mortality and morbidity in our society due to violence. Rapid action and good resuscitation with right decision of good skill hands cardiac surgeon will improve the outcome of the results. DOI:https://doi.org/10.26505/DJM.17024680526